PENGARUH STRUKTUR MODAL DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Rezki Arianty Akob (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study aims to identify and analyze The Effect of Capital Structure and Managerial Ownership on Dividend Policy in Manufacturing Company in Indonesia Stock Exchange. This research was conducted at all manufacturing companies in the Indonesia Stock Exchange. The amount of the total sample of 14 companies with over 5 years of data collection, through a purposive sampling method. To achieve these objectives, the method used descriptive analysis, due diligence research instrument (classical assumption), multiple regression analysis, and hypothesis testing (test f) simultaneously / together and (t test) partial / alone. Based on the results of data analysis and hypothesis testing showed that the F test results indicate that variables consisting of Capital Structure and Managerial Ownership simultaneously have a significant effect on Dividend Policy. The t Test result for Capital Structure variable has a negative and significant effect on Dividend Policy while Managerial Ownership variable is partially negative but not significant to the Dividen Policy in Manufacturing Company in Indonesia Stock Exchange Year 2012-2016.